Héritage d’un nom / héritage d’un art : Daddy #3 de Giulia Andreani - Vialle, Pierre (Romanica Silesiana)
The work Daddy #3 (2012) by Italian artist Giulia Andreani, inspired by a photographic archive, represents Heinrich Himmler with his daughter Gudrun. By means of adapting the photographic image into painting, the artist evokes the burden, sometimes heavy to carry, of family legacies. Moreover, Daddy #3 reveals Andreani’s interest in the woman artist figure, and in the issue of artistic heritage. The painting, which provokes one to ponder the political uses of the image of the family, can also be seen as one of the rare works of art representing an emotional relationship between a father and his daughter.